Pengaruh Teknik Penirisan Menggunakan Spinner Terhadap Mutu Produk Teriyummy - M Ibrahim; Ernawati (Jurnal Ilmu Pertanian dan Perikanan, 2025)
This study aims to evaluate the effect of the draining technique using a spinner on the quality of the Teriyummy product, a coin-shaped anchovy rempeyek. The draining technique plays a crucial role in determining the sensory quality, moisture content, and ash content of processed food products. This research employed two draining methods: manual and spinner-based, with three different draining durations (9, 12, and 15 minutes). The parameters tested included sensory attributes (appearance, aroma, taste, and texture), moisture content, and ash content. Sensory evaluation showed that all treatments met the SNI 2346:2015 quality standards, except for texture. The spinner method performed better in taste and texture, while the manual method excelled in appearance and aroma. Moisture content tests revealed a significant difference, with the lowest moisture value observed in the 12-minute spinner treatment (0.016%), indicating efficient moisture reduction. Ash content tests showed no significant differences between treatments; however, the spinner method provided more consistent and hygienic results. ANOVA analysis confirmed that the spinner method had a statistically significant effect on moisture content but not on ash content. Thus, the spinner draining technique is more effective in improving the overall quality of Teriyummy products.